2018
DOI: 10.3390/ijerph15092028
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Risk and Mental Disorders

Abstract: n/a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
229
1
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(255 citation statements)
references
References 22 publications
15
229
1
10
Order By: Relevance
“…This suggested that the link between psychiatric disorders and suicide attempts is strong regardless of caustic ingestion or other means of suicide. 26,[35][36][37] Second, advanced age was noticed among cases with PCs, in contrast to our previously reported patient group between 1999 and 2009. 18 The senior population with mental illness had an increasing incidence of caustic ingestion in the past decade.…”
Section: Discussioncontrasting
confidence: 67%
“…This suggested that the link between psychiatric disorders and suicide attempts is strong regardless of caustic ingestion or other means of suicide. 26,[35][36][37] Second, advanced age was noticed among cases with PCs, in contrast to our previously reported patient group between 1999 and 2009. 18 The senior population with mental illness had an increasing incidence of caustic ingestion in the past decade.…”
Section: Discussioncontrasting
confidence: 67%
“…1 Md: Median (minimum to maximum) 2 Combination treatment: psychotropics and psychotherapy (CBT, DBT, PDT or other structured psychotherapy) 3 Mono treatment: psychotherapy without psychotropics 4 Mono treatment: psychotropics without psychotherapy 5 Other supportive interventions 6 All patients with ECT were prescribed psychotropic drugs. Two ECT cases (controls) also received psychotherapy 7 Somatic specialist medical inpatient treatment because of somatic comorbidity.…”
Section: Provision Of Somatic Inpatient Carementioning
confidence: 99%
“…Suicide rates and suicide attempts are often associated with a diagnosis of severe psychiatric or somatic illness [4,5], and vary across lifetime and gender [4]. It is important to note that around 90% of individuals who commit suicide have a documented history of a psychiatric disease [6][7][8]. The psychiatric disorders with a high lifetime risk of suicide are the affective disorders [9], particularly bipolar disorder [10], alcohol or substance use disorders [11,12], schizophrenia [13,14], and personality disorders [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…(Saks, 2004). It is worth mentioning that untreated mental illness most commonly (about 90% of the time) leads to suicide (Brådvik, 2018). These numbers signal the essential need to fi nd effective ways to de-escalate this problem and provide legal tools to help individuals seek help.…”
Section: Supporting Attitudes Towards Of Mhadsmentioning
confidence: 99%